2005
DOI: 10.1002/bjs.4798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warm-up on exercise capacity, platelet activation and platelet–leucocyte aggregation in patients with claudication

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…A sample size of 16 participants per group have 80% power, 5% significance (two‐tailed) to detect one standard deviation score ‘large effect size’ for cIMT between cases and controls. The sample size for platelet function was calculated using the Mann–Whitney U‐ test for continuous data and an ‘effect size’ between 1·12–1·25 . A sample size of 18–20 per group allows us to detect an effect size of 1·12 (or larger) with 80% power, 20% attrition and 5% significance (two‐tailed).…”
Section: Methodsmentioning
confidence: 92%
“…A sample size of 16 participants per group have 80% power, 5% significance (two‐tailed) to detect one standard deviation score ‘large effect size’ for cIMT between cases and controls. The sample size for platelet function was calculated using the Mann–Whitney U‐ test for continuous data and an ‘effect size’ between 1·12–1·25 . A sample size of 18–20 per group allows us to detect an effect size of 1·12 (or larger) with 80% power, 20% attrition and 5% significance (two‐tailed).…”
Section: Methodsmentioning
confidence: 92%
“…The sample size for platelet function was powered using the Mann–Whitney U test for continuous data [ 23 ] and an ‘effect size’ between 1.12–1.25 for changes in P-selectin expression in unstimulated samples [ 24 , 25 ]. A sample size of 18 per group allow us to detect an effect size of 1.12 (or larger) with 80% power, 20% attrition and 5% significance (two-tailed) between cases and controls.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with stable coronary disease, RIC attenuated platelet activation in response to adenosine diphosphate (ADP) and exercise 18 and in patients with claudication, warm-up (a phenomenon akin to IPC) prior to exercise attenuated the exercise-induced increase in platelet-neutrophil and platelet-leukocyte activation. 49 In patients undergoing ablation for atrial fibrillation, RIPC reduced platelet activation in response to ADP, including the formation of monocyteplatelet aggregates. 19 Other studies found that intermittent upper arm IR reduced platelet activation and aggregation in response to ADP in patients with stable angina undergoing angiography or elective angioplasty.…”
Section: Possible Mechanismsmentioning
confidence: 99%